2018
DOI: 10.1080/20008198.2018.1541697
|View full text |Cite
|
Sign up to set email alerts
|

How do men with severe sexual and physical childhood traumatization experience trauma-stabilizing group treatment? A qualitative study

Abstract: Background: Exposure to potentially traumatizing events, defined as events involving actual or threatened death or serious injury, is associated with an elevated risk of developing enduring physical, psychological and social problems. Complex post-traumatic stress disorder (PTSD) is a disorder that can occur after prolonged and repeated trauma. At least 30% of the sexually abused population is male, but in spite of this fact, treatment research focusing on male victims is virtually non-existent in comparison t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
1
9
0
2
Order By: Relevance
“…It is noteworthy, that many participants found it the most challenging for self-practice that they did not have any verbal instructions. These observations are in line with the results of other studies: It has been shown that the internal structure of group therapy sessions helps traumatized patients to stay focused on the present, while preventing intrusive symptoms and dissociation [38,43]. Except for one participant, the participants stated that the intimate atmosphere in the group session room transported a feeling of safety.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It is noteworthy, that many participants found it the most challenging for self-practice that they did not have any verbal instructions. These observations are in line with the results of other studies: It has been shown that the internal structure of group therapy sessions helps traumatized patients to stay focused on the present, while preventing intrusive symptoms and dissociation [38,43]. Except for one participant, the participants stated that the intimate atmosphere in the group session room transported a feeling of safety.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, some participants stated that they missed the presence of the other group members during self-practice. In line with these observations, different studies evaluating the benefits of group therapy for adults with traumatic experiences have found that socialization, personal exchange, de-stigmatization, and cohesiveness can improve mental health [12,13,37,38,39,40]. However, two out of three participants left the group because the other group members made them feel uncomfortable.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Cuatro artículos se centraron en las inter venciones terapéuticas a víctimas de VSI masculina, con predo minio de enfoq ues cognitivo-conductuales basados en terapias gr upales masculinas y en aspectos co m o la m otivación en la participación (22,30,(45)(46). Uno de los estudios encontró q ue los puntos de inflexión en la vivencia posterior a la VSI, relacionados con la revelación del ASI y la búsq ueda de justicia, son deter minados por factores co m o las relaciones entre las víctimas y los gr upos o profesionales de apoyo, el insight y los nuevos significados, la transfor mación espiritual y la necesidad de cam bio, y la co m unicación orientada hacia la acción (22).…”
Section: Atención Terapéutic Aunclassified
“…El estudio de Taylor, Goshe, Marq uez, Safren y O'Cleirigh (30) examinó la relación entre la terapia cognitivo-conductual y la reducción del estrés postraumático asociado con el ASI; encontró q ue esta terapéutica mejoraba los co m portamientos de autocuidado, particular mente, q ue la m otivación para participar en terapias de ayuda favorece la reducción de co m portamientos de riesgo en el ám bito de la sexualidad. Finalmente, otra investigación reportó q ue en la aceptación de los gr upos de ayuda es fundamental la atmósfera de gr upo, la m otivación y el aprendizaje, y de for ma destacada la búsq ueda tem prana co m o parte fundamental para estabilizar el trauma (46).…”
Section: Atención Terapéutic Aunclassified